Efeito da amônia sobre a fertilização artificial de ovócitos e no desenvolvimento inicial do jundiá cinza (Rhamdia quelen; Siluriformes, Heptapteridae) - Vidal, Eléxio (2012)
The aim study it had as objective to evaluate the effect of different ammonia levels, on the parameters of sperm motility, the artificial fertilization and the early development of jundia (Rhamdia quelen; Siluriformes, Heptapteridae). The semen was activated using the dilution of 1:70 (semen:water) and evaluated by the CASA method. It was considered as treatment water contending 0,06; 0,28; 0,50; 0,77 and 0,84 mg of total ammonia.water-1 L, so for sperm activation as for fertilization and incubation of the oocytes. The incubation was composed for a recirculation system of 250L for each treatment, with four incubators, being that each incubator approximately had useful volume of 2,5L with 3,800 eggs. Had been evaluated the parameters of sperm motility, fertilization rate, thermal unit accumulated for beginning and ending of the hatching, hatching rate, embryonic and percentile development of normal larvae. The results had been submitted the analysis of variance and the analysis of regression to a 5% of probability level. The ammonia levels gifts in the water did not interfere on the evaluated parameters (p> 0,05), except about to the early embryonic development, where the embryos displayed to the biggest levels of contamination for ammonia had presented greaters (p>0,05) closing of the blastopore rates. In general way, the presence of until 0,84mg of total ammonia. Water-1 L speeds up the embryonic early development but they do not interfere with the fertilization and hatching rates.